Meningkatkan Hasil Belajar Siswa Melalui Implementasi Model Pembelajaran Jigsaw pada Mata Pelaharan IPA Tema 5 Subtema 1 Ekosistem Kelas V SD Negeri 24 Toboali - Marwiyah Marwiyah; Didi Kriswanto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
This study aims to improve student learning outcomes through the implementation of the jigsaw learning model in the Science subject, Theme 5 Sub-theme 1 Ecosystems for class V at SD Negeri 24 Toboali. This research is a type of classroom action research. The subjects in this study were all V grade students at SD Negeri 24 Toboali. The object of this research is the results of student learning in Science subject, Theme 5 Sub-theme 1 Ecosystem class V. Data collection techniques used written tests, observation, and documentation. This research was said to be successful if 80% of students achieved KKM, namely 73. The results showed that the implementation of the Jigsaw Learning Model in Science learning Theme 5 Sub-theme 1 Ecosystem had a positive and significant effect on improving student learning outcomes. This is evidenced by the average score in the first cycle, which was 69.79 with a completeness percentage of 54.17% and in the second cycle, the average value increased significantly to 80.20 with a completeness percentage of 87.50%. Furthermore, the increase in the percentage of self-confidence assessment in the first cycle was 58.25%, it increased in the second cycle to 83.25%, and the assessment of the attitude of cooperation in the first cycle was 69.75%, which increased in the second cycle to 88.50%.